Design, set up and commissioning of a test facility for smokeless rich diesel combustion research - King, Timothy Cole (Sasol Advanced Fuels Laboratory, 2017)
Low Temperature Combustion (LTC) is a strategy that harnesses the properties of exhaust gas, through the use of large quantities of exhaust gas recirculation (EGR), to reduce the peak combustion temperatures below that favoured by the formation processes of oxides of nitrogen (Ox) and those of soot. There is interest within the fuels research community in investigating the effects of diesel fuel formulations on LTC, using a suitable engine test platform. The objective of this study was to design and set up a test apparatus capable of achieving LTC in a diesel research engine, that could subsequently be used to study LTC behaviour with different fuels. In addition, it was necessary to present test data demonstrating the engine's performance, in terms of engine-out emissions and indicated specific fuel consumption (ISFC), transitioning between conventional diesel combustion (CDC) and LTC. The mechanical, electrical and control requirements for attaining CDC and LTC conditions were investigated in the literature and through consultations with experts in the fuels research field. These requirements were distilled into a definitive System Requirement Specification.